Przedmowa. Rozważania człowieka niepolitycznego (przełożył Jacek Kępa) - Mann, Tomasz (Przestrzenie Teorii, 2015)
“The Preface” was finished after the work on “Reflections of a unpolitical Man” and explains the reasons behind its creation. Thomas Mann decided that armed conflict between Germany and the West was the result of different perspectives. Democracy damages the world order and German values. The greatest advocate of democracy among Germans is the civilization’s man of letters. Mann undermines the value of his art and gives reasons for the disagreements with this revolutio-nary knowledge, which he calls “The new Pathos”. He develops the theory of the greatness of Germans as a nonpolitical nationality, recognizing Martin Luther as a reflection of this theory. He mentions the great minds of the 18th and 19th centuries to emphasize the most crucial differen- ces, seeing in himself a child of the 19th century. In conclusion, Mann claims that his opposition to democracy hastens its victory.